Dinâmica de abastecimento dos produtos da agricultura familiar para a alimentação escolar: o caso do município de Araripe-CE. - Marques, Amanda de Andrade (2013)
The National School Nutrition Programme (PNAE) has existed for over 50 years in Brazil, its goal is to contribute to the growth and biopsychosocial development, learning, school performance and training healthy eating habits of students. Throughout its existence, the PNAE has undergone changes in its operation. One of these changes occurred in 2009 with the mandatory inclusion of local produce, family farming and / or their organizations in school meals. Therefore, we intend to analyze the dynamics of supply foodstuff Family Farming for the School Feeding Program in Araripe-Ceará. This is a case study, conducted through semi-structured interviews and observation spot with journaling field. Study participants were fourteen farmers suppliers of food to schools, three Presidents of Associations of Family Farmers, the nutritionist responsible for technical School Feeding Program, the Technical EMATER (organization representing family farmers) the local coordinator of purchases family farming for school feeding and school principal selected. To examine the issues used the thematic content analysis, following these phases Pre-analysis, exploration of the material in order to reach the core of understanding the text, to achieve the thematic categories. Finally, the interpretation of statements, where the distribution took place in two categories (difficulties and benefits in view of farmers) and the reflections that arose around those occurring later interpretation and discussion of the theoretical light. The study was approved by the Ethics Committee of the Health Science Center, Federal University of Paraíba, under protocol # 0339/11. It was observed that among the difficulties pointed out by farmers among the most frequent words were Payment, Transport and Physical Structure. As for the benefit, Job Opportunity and guaranteed income. Thus, it is clear that analyzing the dynamics of supply of products of family farming for school feeding is of great value, since it is a recent resolution and that municipalities are still adjusting to this new system. Some alternatives were created locally to facilitate and encourage the supply of farmers and ensure that food reaches the schools. Among them, there is the creation of a schedule for delivery of agricultural family; different menus for schools located in rural and urban areas that receive products from family farms, installation of processed food factories since this city suffers with the dry weather most of the year and it is necessary that other products entering the school feeding; incentive associations by the municipal administration, adding, in this way, value to the final product; partnerships with SEBRAE, EMATER to empower farmers. It is noticed that the specifications determined by law and resolutions of bodies often turn away from the reality of the municipalities. It is necessary to create the means to effect this process locally so that students and farmers are met satisfactorily through this relationship school meals and family farming.